Alcohol Consumption, HDL-Cholesterol and Incidence of Colon and Rectal Cancer: A Prospective Cohort Study Including 250, 010 Participants. (19th February 2021) - Tverdal, Aage; Høiseth, Gudrun; Magnus, Per; Næss, Øyvind; Selmer, Randi; Knudsen, Gun Peggy; Mørland, Jørg
Abstract: Aims: Alcohol consumption has been linked to colorectal cancer (CRC) and also to the high-density lipoprotein cholesterol level (HDL-C). HDL-C has been associated with the incidence of CRC. The aim of this study was to investigate the association between self-reported alcohol consumption, HDL-C and incidence of CRC, separately for the two sites. Methods: Altogether, 250, 010 participants in Norwegian surveys have been followed-up for an average of 18 years with respect to a first-time outcome of colon or rectal cancer. During follow-up, 3023 and 1439 colon and rectal cancers were registered. Results: For men, the HR per 1 drink per day was 1.05 with 95% confidence interval (0.98–1.12) for colon and 1.08 (1.02–1.15) for rectal cancer. The corresponding figures for women were 1.03 (0.97–1.10) and 1.05 (1.00–1.10). There was a positive association between alcohol consumption and HDL-C. HDL-C was inversely associated with colon cancer in men (0.74 (0.62–0.89) per 1 mmol/l) and positively associated with rectal cancer, although not statistically significant (1.15 (0.92–1.44). A robust regression that assigned weights to each observation and exclusion of weights ≤ 0.1 increased the HRs per 1 drink per day and decreased the HR per 1 mmol/l for colon cancer. The associations with rectal cancer remained unchanged. Conclusion: Our results support a positive association between alcohol consumption and colon and rectal cancer, most pronounced for rectal cancer. Considering the positive relation between alcohol consumption and HDL-C, the inverse association between HDL-C and colon cancer in men remains unsettled. Abstract : Short Summary : This study showed that the relation between alcohol consumption is somewhat stronger for rectal cancer than for colon cancer. Although there is a positive relation between levels of HDL and alcohol consumption, the relation between HDL and colon cancer in men is inverse. This finding warrants further studies.